FISCAL POLICY IN AN ISLAMIC PERSPECTIVE - Kiddri, Laylatul; Savira Zahrah, Devi (ISTISMAR, 2020)
Fiscal politics are rules that aim to manage government income and expenditure in order to stabilize and encourage economic development. The instruments of monetary regulation are state income and expenditure. Every year, the government prepares a provincial income and expenditure budget which is given to the DPR for approval as the APBN. If economic development has a significant influence on the fiscal politics implemented in the APBN. Fiscal politics was born from awareness of the impact of state income and expenditure. This monetary rule is included in the discussion of Islamic economics. In Islamic economics, monetary rules were already well known during the time of the Prophet and his companions. Islamic economic ideas already existed during the Islamic regime of Medina and included ready-made ideas that could only be used as an alternative to the modern financial system. Accepting classical Islamic financial concepts without reconstructing them in modern situations only turns back time to simpler times. Recognizing zakat as the basis of Islamic finance and then rejecting taxes only leads to the ideal of Islamic finance.